Pengukuran Penerimaan Aplikasi E-Resources Center Stikom Surabaya Menggunakan Metode Technology Acceptance Model 3 - Meifa, Prabu Prasetya; Sudarmaningtyas, Pantjawati; Suhandiah, Sri (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Stikom library has service that aims to make it easy for members to access the information and utilization of allkind of printed work and digital works. One of them is accommodating the digital works thaht is E-resources center. Since 2010-2015 it has been downloaded at 8.55 % facility  of jurnal, 14.86% in facility of video, and 22.07 % . Information technology successfully if the user can accept it.User behavior also effect to successful of that application. One method that can measure is the technology acceptance model 3 (TAM3). TAM 3 discusses the interlationships of the construct (nomological netrwork) determine of why individuals adopt and use the information technology (IT). Based on analyzing the application of e-resources center aggred and received because the data showed the mean 2.930, and the most value is what the benefit at e-resources is information system positive 0.973 influence perceived usefulness  0. it is clear that the student interest using e-resources center and influenced by intention to use regularly.